Analysis of Phonological Errors in the Pronunciation of Sholawat Badar on the Tiktok platform - Azkiyatunnisa; Mugy Nugraha; Minatur Rokhim (Jurnal Al-Maqoyis, 2025)
The rapid development of technology has a major impact on human life, including the emergence of the latest innovations, such as the emergence of Tiktok social media. This platform is not only used for communication and information dissemination, but also as a medium for cultural exchange that is thick with Islamic values such as the recitation of Sholawat Badr. This trend is widely followed, both by Arabic and non-Arabic speakers, including Indonesians. However, the difference between Arabic and Indonesian phonemes causes many errors in pronunciation. This study aims to identify phonological errors in six videos of recitation of sholawat badar with non-Arabic speakers, namely speakers with Indonesian as their mother tongue, on the tiktok platform under the account names @elvoacapella, @religi_favoritku, @hits.records, @trisna2704_, @craion31official, and @sigmaent. This research method is qualitative with data collection techniques used are documentation techniques, free listening techniques, and note-taking techniques. Data analysis was carried out through the stages of collecting samples, identifying and classifying, explaining, and evaluating errors. The results found articulation errors between phonemes that have slight differences in makhraj and sifat as many as 21 forms.